INTERNATIONAL MECHANISM FOR PREVENTION OF TRAFFICKING OF WOMEN AND THE LEGAL ANGLE RELATED TO THIS - Mishra, Rashmi; Srivastava, J.S.P. (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The research paper titled ‘‘International Mechanisms for Prevention of Trafficking of Women and The Legal Angle related to this" deals with the multifaceted and critical issue of trafficking of women, exploring the intricate web of international mechanisms and legal frameworks that seek to prevent and address this grave violation of human rights. The paper delves into the systemic factors, vulnerabilities, and repercussions of trafficking, with a specific focus on its disproportionate impact on women. The research systematically examines a range of international mechanisms, agreements, conventions, and protocols that have been established to combat trafficking, shedding light on the collaborative efforts of the nations and many international organizations to eradicate this heinous practice. This research paper examines the global frameworks established to prevent and address trafficking in women, and explores the legal dimensions and implications of these frameworks. Drawing on a comprehensive array of legal sources, case studies, and empirical data, the paper dissects the legal dimensions of trafficking, analysing the complexities of defining and prosecuting this crime on a global scale. It scrutinizes the challenges posed by differing legal definitions and interpretations across jurisdictions, highlighting the necessity for harmonization and standardization of legal frameworks to effectively address trafficking and provide justice for victims. The paper also investigates the vital role of international organizations, including the United Nations and its various agencies, in developing and executing strategies for prevention, victim protection, and prosecution. Ultimately, the research paper underscores the urgent necessity for a unified and coordinated international strategy to tackle the trafficking of women. It underscores the importance of aligning legal frameworks, enhancing cross-border cooperation, and fostering a global commitment to eradicating this abhorrent practice. By shedding light on the intricate web of international mechanisms and legal angles surrounding trafficking of women, the research paper contributes valuable insights and recommendations to the ongoing global efforts to prevent and address this deeply concerning violation of human rights.